If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3x + 6) = 0 Reorder the terms: 9(6 + 3x) = 0 (6 * 9 + 3x * 9) = 0 (54 + 27x) = 0 Solving 54 + 27x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 27x = 0 + -54 Combine like terms: 54 + -54 = 0 0 + 27x = 0 + -54 27x = 0 + -54 Combine like terms: 0 + -54 = -54 27x = -54 Divide each side by '27'. x = -2 Simplifying x = -2
| (5x+12)+(6x-10)=360 | | 2x-5=6x-14 | | Fx=2x^2-3x+1 | | Y=-2(x-(1+I))(x-(1-I)) | | 5w+b=-4-5w | | X-.90x=72 | | 2f-g=5e | | 1/3p=14 | | -30cot^2(x)+15cot(x)-120=0 | | 5w+b=-4-5w-2 | | (4a+12)(5a-20)=0 | | .75a+7=a-1 | | 5(x+2)-(x-5)(x-5)=(2x-3)(2x+3)+19 | | 5x+45=x+21 | | a=p-nt | | -8(4n+3)=30-5n | | 3z+3z=5z+5 | | 1.6(2.2)2x=4(4.1)x | | 18(2.1)x=(6.6)x | | .90x+72=y | | p^3(36p^2q^8)^(1/2) | | -2/-(3/8) | | 72=.90x | | (-1/4)×(-3/7) | | 8s=3(5+5) | | x=4-8x/21x | | 4z^2+31=24z | | X*X-2*X+1=40 | | 7m+5=2m+20 | | -1.6(2y+15)=-1.2(2y+-10) | | -1-5b=-3(b+5)-2 | | -1.6(27+15)=-1.2(2y-10) |